THE EFFECT OF FORTIFICATED OF MUSSEL MEAT FLOUR ON CONE WAFER TOWARDS CONSUMER ACCEPTANCE - Gaol, Anggi Julisna Lumban; Sari, N. Ira; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study was aimed to determine the effect of fortification of  mussel meat flour on cone wafers towards consumer acceptance. The treatment was the addition of mussel meat flour with different concentration which consisted of 0% mussel flour (W0),2,5% 0f mussel flour (W1),5% of mussel flour (W2),and 7,5% of mussel flour (W3).Analysis parameters include organoleptic test (appearance, taste, aroma, texture), and proximate analysis. Based on the result that the addition of 5% of mussel meat flour on cone wafers was the best treatment with the characteristics yellowish color, the aroma a little show rancid from mussel meat flour, sweetness, solid texture, meanwhile for ash, moisture, protein, and fat content was 1,63%, 3,11%, 13,39% 17,59%. Keywords: mussel meat flour, cone wafer, consumer acceptance